1998
DOI: 10.1038/sj.sc.3100705
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma PSA in spinal cord injured men: a preliminary report

Abstract: Objective: The aim of the study was to evaluate the impact of spinal cord injury on seminal plasma PSA concentration. Material: Semen obtained from normal controls (n=20) and patients (n=16) with spinal cord injury. Results: The concentration of prostate speci®c antigen in seminal plasma depended on the level of spinal cord injury, with signi®cantly lower concentrations in patients with spinal cord lesions below T7 compared to both normal age-matched controls (P=0.007) and patients with spinal cord injuries at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Moreover, ACPP, a tyrosine phosphatase that dephosphorylates large numbers of substrates and which has been widely used a biomarker for prostate cancer (51), was observed to be around sevenfold more abundant in the SP of controls. Thus, our proteomic results strongly support what other studies have only hypothesized (12,52), i.e. that a prostatic dysfunction could somehow be involved in SCI related infertility.…”
Section: Qualitative Map Of the Human Seminal Plasma Proteome-supporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, ACPP, a tyrosine phosphatase that dephosphorylates large numbers of substrates and which has been widely used a biomarker for prostate cancer (51), was observed to be around sevenfold more abundant in the SP of controls. Thus, our proteomic results strongly support what other studies have only hypothesized (12,52), i.e. that a prostatic dysfunction could somehow be involved in SCI related infertility.…”
Section: Qualitative Map Of the Human Seminal Plasma Proteome-supporting
confidence: 81%
“…The neurogenic stimulation of the male accessory sexual glands including the prostate arises from sympathetic nerves from the thoracolumbar spinal cord (T11-L2) and from parasympathetic nerves from the sacral spinal cord (S1-S4) (54). Brasso et al reported that SP concentrations of KLK3 were significantly lower in SCI patients with lesions below T7 compared with patients with lesions at or above this level (52). Studies have shown that the prostate gland is smaller in men with SCI compared with healthy, noninjured men, and that this effect may be because of a prolonged central (rather than peripheral) desinnervation of the prostate gland (55).…”
Section: Qualitative Map Of the Human Seminal Plasma Proteome-mentioning
confidence: 99%
“…Seminal plasma PSA concentration is approximately 10 5 -10 6 times higher than serum PSA concentration and the majority of PSA in seminal plasma is present in the catalytically active single-chain form. 23 Brasso et al 24 evaluated the seminal plasma PSA concentrations in 16 patients with SCI compared to 20 normal controls. The concentration of PSA in seminal plasma depended on the level of SCI, with significantly lower concentrations in patients with lesions below T7 compared to both normal age-matched controls and patients with lesions at or above T7.…”
Section: Seminal Plasma Prostate-specific Antigen Levels In Men With mentioning
confidence: 99%
“…The results are shown in Table 3. 18,20,24 Prostate cancer diagnosis in men with spinal cord injury It has been theorized that central denervation of an organ is protective against malignancy and changes in Prostate activity and prostate cancer SCI HB Shim et al the hypothalamic-pituitary-gonadal axis but no persuasive data are available. Historically, since SCI patients rarely survived into the years during which prostate cancer becomes a significant medical issue, they were not screened and death from prostate cancer in patients with SCI was rare.…”
Section: Seminal Plasma Prostate-specific Antigen Levels In Men With mentioning
confidence: 99%
“…However, most authors agree that the best motility is obtained when semen is collected by VE than by electroejaculation. 15 Brasso et al 16 have studied seminal PSA using either VE or electroejaculation for collecting semen. They have not found statistical difference between the two methods.…”
Section: Discussionmentioning
confidence: 99%